The synovial membrane in osteoarthritis: a histological study including the characterisation of the cellular infiltrate present in inflammatory osteoarthritis using monoclonal antibodies. Issue 4 (April 1988) - Revell, P A; Mayston, V; Lalor, P; Mapp, P
Abstract : Inflammatory infiltration of the synovial membrane has been described in a proportion of cases of osteoarthritis (OA). Using conventional histology, lymphoid follicles, diffuse fibrosis, and perivascular fibrosis were shown to be present to a significantly greater extent and in more synovial membranes in osteoarthritis than in those cases where there was a mechanical or traumatic background to the joint disease. Calcium pyrophosphate dihydrate crystals (five patients) and detritus fragments of bone and cartilage (seven patients) were present in small numbers of the total cases of OA (38) studied. Neither of these features was related to the presence of an inflammatory infiltrate. Examination of 20 osteoarthritic synovial membranes using monoclonal antibodies showed the presence of lymphoid follicles containing T helper and T suppressor lymphocytes, B lymphocytes, and macrophages expressing HLA-DR in five cases. The T helper:suppressor ratio varied between 1:1 and 2.5:1 in these follicles. In addition, half of the OA samples, including these five cases, showed the presence of a diffuse cellular infiltrate containing T and B lymphocytes and macrophages, which were HLA-DR positive. Granulocytes were present in this diffuse infiltrate in those cases containing lymphoid follicles. The results confirm the presence of an inflammatory form of osteoarthritis but also show that the proportions of lymphoid cells are not the same as those considered to be typical of rheumatoid arthritis.